Effectiveness Of Implementing Grammatical And Translation Methods Through A Student-Centered Approach To Improve Reading Skills In Teaching Arabic At Nurul Falah Senior High School - Alami, Robi; Hidayat, Hakmi; Roviana, Roviana (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
AbstractThis research is an experimental study which aims to determine the effectiveness of implementing grammatical and translation methods through a student-centered approach to improve reading skills in teaching Arabic for eleventh grade students at Nurul Falah Senior High School (SMA) Pekanbaru Riau. The formulation of the problem in this research is